Da de polske jøder kom til Danmark - Smedegaard, Rikke (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
In the late 1960s, the Communist Party in Poland launched an anti-Jewish campaign, which forced the remaining Jews in Poland to emigrate. The Danish government conducted a very liberal policy in order to help as many Polish-Jewish refugees as possible. Emphasis was placed on the so-called ‘humanitarian tradition’ as Denmark had previously helped to save Jews. From a political point of view there was apparently no doubt that this was a viable and sufficient argument. At no time were references made to the UN Refugee Convention, which Denmark was the first country to ratify, and which would otherwise have been an evident and clear-cut argument. From 1969-73, between 2,600 and 3,000 Polish-Jewish refugees came to Denmark. In the fall of 1969, about 100 refugees arrived a week. This was an unprecedented number in Danish history, which led to challenges logistically speaking. In order to not unnecessarily provoke Poland, the Danish authorities decided to avoid any publicity regarding the arrival of the Polish Jews in Denmark. Only after Foreign Minister Poul Hartling had answered a question about the subject in the Danish Parliament, the press started addressing the topic. Hereafter the media showed great interest in writing about the Polish-Jewish refugees. Thus we see that also the press acted in accordance with the Danish self-image and cooperated with the authorities to ensure that the rescue of Jews from Poland could be as successful as possible. This is also reflected in the media coverage itself based on a representative section of the Danish media landscape, where the support for the refugees was predominant.